2021
DOI: 10.3390/ma14164414
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast-like Cell Proliferation, ALP Activity and Photocatalytic Activity on Sintered Anatase and Rutile Titanium Dioxide

Abstract: This study aimed to create a biomaterial from titanium dioxide (TiO2), which has been known to have photocatalytic and bone formation promoting effects. I expected that anatase titanium dioxide-based implants could promote bone augmentation and induce bone formation. Powdery anatase TiO2 was compression molded and sintered at 700, 800, 900, and 1000 °C to prepare sintered compact samples. X-ray diffraction and scanning electron microscopy were used to observe the surface of these samples. Furthermore, mouse os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Meanwhile, to give full play to the surface modification effect of UV functionalization technology, some semiconductor materials can be used as photocatalysts to improve the irradiation efficiency of UV light . The principle is that under UV irradiation, electrons on the valence band can leap to the conduction band to form photogenerated electrons and holes on the valence band, and then the photogenerated electrons and holes react with H 2 O and O 2 adsorbed on the surface of photocatalyst to generate hydroxyl radicals, radicals, and other active groups.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, to give full play to the surface modification effect of UV functionalization technology, some semiconductor materials can be used as photocatalysts to improve the irradiation efficiency of UV light . The principle is that under UV irradiation, electrons on the valence band can leap to the conduction band to form photogenerated electrons and holes on the valence band, and then the photogenerated electrons and holes react with H 2 O and O 2 adsorbed on the surface of photocatalyst to generate hydroxyl radicals, radicals, and other active groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of these wear particles on the osteoblasts based on their concentration, size, and morphology is not well demonstrated. Studies have shown that TiO 2 nanoparticles have varying effects on osteoblasts and osteoblast-like cells [ 10 , 11 ]. Osteogenic inhibition and bone loss induced by the wear of titanium alloy are crucial in the instigation of peri-prosthetic osteolysis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%